2. Curriculum (Journal of Parents and Teachers, 2026)
The concept of curriculum is explained as a flexible plan that priorities problem solving and practical application over memorization, integrating the intellectual, physical and emotional dimensions of the student. It highlights an open and flexible model that allows teaching to be adapted to the reality of each school. Increasingly, there is a search for education that is connected to real life.
Keywords: Curriculum, education, reality and reform.